Pre-operative work-up before bariatric surgery: Should ultrasonography and upper gastrointestinal endoscopy be done routinely? (Annals of Medical Research, 2021)
None
Keywords: Bariatric Surgery; Ultrasonography; Endoscopy; Work-Up.